Penentuan Lingkungan Batimetri Formasi Baturaja dan Formasi Gumai, Daerah Negeribatin dan Sekitarnya, Kabupaten Ogan Komering Ulu Selatan, Sumatera Selatan - Hemalia Margareta; Idarwati (Mataram University, 2026)
The Negeribatin area, Ogan Komering Ulu Selatan Regency, South Sumatra Province, is part of the South Sumatra Basin and is composed of Tertiary sedimentary rock units, particularly the Baturaja Formation and the Gumai Formation. This study aimed to determine and reconstruct the bathymetric environments of these two formations based on lithological characteristics and the types of benthic foraminifera. The research methods included field observations and laboratory paleontological analyses involving rock sample preparation, sieving, and identification of benthic foraminifera using a microscope. The interpretation of bathymetric environments was conducted based on the depth range of benthic foraminifera habitats. The results show that the Baturaja Formation is composed of calcarenite limestone and reef limestone, indicating a marginal to middle neritic depositional environment at depths of approximately ±14–183 m. Meanwhile, the Gumai Formation, composed of sandstone and claystone, indicates a transitional to middle neritic depositional environment with a depth range of approximately ±12–183 m. The transition from carbonate rocks to clastic rocks reflects an increase in depositional depth related to the development of geological structures in the area. This study contributes to a better understanding of the evolution of depositional environments and sedimentary systems in the South Sumatra Basin.